Peran Majelis Taklim Masjid At-Tawwabin dalam Peningkatan Pemahaman Keagamaan Masyarakat Kota Medan, Sumatera Utara - Ananda Zahwa; Khoiriyah Azzahra Hasibuan; Wahyu Andreansyah Siregar; Afril Viqri; Hendra Kurniawan (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study examines the role of Majelis Taklim Masjid At-Tawwabin in enhancing religious understanding among the Muslim community in Medan City, North Sumatra. Majelis taklim is a non-formal Islamic educational institution that functions as a medium for religious learning, moral development, and social reinforcement within the community. This research employs a qualitative approach using field research methods. Data were collected through in-depth interviews, field observations, and documentation involving three administrators of the majelis taklim and two active congregants. The findings indicate that Majelis Taklim Masjid At-Tawwabin plays a significant role in improving religious knowledge, strengthening worship practices, and fostering positive religious attitudes among community members. Well-organized management, relevant religious materials, and participatory teaching methods contribute to the effectiveness of majelis taklim activities. This study concludes that mosque-based majelis taklim has strong potential as a sustainable model of community-based religious education.